PENGARUH MODEL PEMBELAJARAN BERBASIS FENOMENA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Ardiyanti, Farida; Winarti, Winarti (Kaunia: Integration and Interconnection Islam and Science Journal, 2013)
The critical thinking skill is crucial given the earlier time in the proces of learning science. It is needed various kind of model of learning to teach the critical thinking skill to student. This research is aimed to know whether the learning based phenomenon is able to improve the critical thinking skill student in elementary school. This research is quasi-experimental. The population in this is elementary school students,